The Implementation of Corporate Governance and Risk Management in a Small-Package Delivery Service Company: The Case Study of PT.XYZ - Mulianto Tarigan; M. L. Denny Tewu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper examines the implementation of corporate governance (CG) and risk management (RM) in a small-package delivery service (SPDS) company in Indonesia, namely PT.XYZ Express, an Indonesian private company owned by several Indonesian shareholders. The principles of corporate governance (CG) have been introduced and implemented in the company, however some challenges occur during the implementation and elaborated in this study.  Qualitative research method is used in this study with observations and documents collected from external and internal of the company. The purpose of this study is (1) to provide an overview of the current implementation of the principles of corporate governance and risk management, (2) to provide risk assessments on the failures related to corporate governance, (3) to provide recommendations for future implementation.